The (in)Functioning of the United Nations Security Council in the Context of Russian Aggression: is it Naive to Expect Change? - Jokšaitė, Adriana; Jakovleva, Kristina (Vilnius University Open Series, 2024)
Russia’s aggression against sovereign Ukraine in February 2022 has once again highlighted the shortcomings of the UNSC mechanism. The UNSC, which continues the work of its predecessor, the League of Nations, and which has the mission of maintaining world peace and security, is incapable, in the context of the war in Ukraine, of adopting the necessary resolutions and other actions that would help to put an end to the ongoing aggression.  The planned reforms of the UNSC have not been implemented in the past, and therefore face the insurmountable obstacle of Russia, one of the 5 permanent members, being the aggressor state and constantly vetoing UNSC resolutions. Both the requirements for amending the UN Charter itself and the voting process legally make it impossible to remove Russia from the UNSC unless the aggressor itself votes to remove its delegation from the UNSC. Observing Russia’s actions during the war in Ukraine, it is safe to say that Russia will not give up the opportunity to continue to enjoy the place in the SC that it took over from the USSR after its collapse in 1991. An analysis of the practice of international law and the historical context in which the UNSC operates leads to the conclusion that the UNSC is currently functioning as an organisation that is unable to fulfil its core functions due to the limitations of the UN Charter. It is hardly possible to revive an organisation in which the aggressor state and the violator of international law have veto power.
Keywords: United Nations; Security Council; Ukraine; war; aggression; United Nations Charter; peace and security; Russia